Impacts of economic sanctions on population health and health system: a study at national and sub-national levels from 2000 to 2020 in Iran - Efat Mohamadi; Alexander Kraemer; Reza Majdzadeh; Morteza Mohamadzade; Marita Mohammadshahi; Mohammad Mehdi Kiani; Fatemeh Ebrahimi; Hakimeh Mostafavi; Alireza Olyaeemanesh; Amirhossein Takian (BMC, 2024)
Abstract Background Formal evidence regarding the effects of sanctions on population health status and the health system is scarse in Iran. Given the intricate and multifaceted nature of sanctions, a nuanced understanding of their impact is imperative. We aimed to investigate the magnitude and effects of sanctions on population health and healthcare system during the last two decades in Iran. Design This is a mixed-methods research. We quantified the impact of sanctions using 28 indicators, i.e. macroeconomic, healthcare resources and health outcomes indicators from 2000 to 2020. The concurrent qualitative study aimed to explore the pathway of the effect by considering perceptions of both patients and health policy makers towards sanctions; Interview data was analyzed using content analysis. Setting This study was conducted in Iran at both national and sub-national levels. Results Our findings revealed that the trend of 11 indicators (39.2%) had changed after the change point in 2009; four indicators (14.2%) significantly deteriorated after the change point. Further, five indicators revealed significant increases during the sanctions period: Out-of-Pocket payment (OOP), household expenditure on food and mortality rates due to Chronic Obstructive Pulmonary Disease (COPD), thalassemia and hypertension. Our qualitative analysis revealed that patients identified availability, cost and quality of medicines and healthcare services as the most significant challenges that compromised population's health. From the policy makers' perspective, the effect of sanctions on health system functions and infrastructures, i.e. economic, political, social, educational and research had significant repercussions on population health. Conclusion We could not find compelling evidence to establish significant associations between the imposition of sanctions and the trend of population health. Nevertheless, our qualitative study revealed people's deteriorating life experiences, e.g. increasing catastrophic health expenditure, limited access to necessary medicine, medical equipment, procedures and interventions, imposed by sanctions, with ultimate reducing impact on the overall quality of life. It seems that sanctions have negatively affected financial and physical access to medication and healthcare services. Nonetheless, Iran has demonstrated remarkable resilience against their highly detrimental effects, maybe due to its established economic infrastructure and healthcare system.